PENYESUAIAN SOSIAL REMAJA DITINJAU DARI PERAN IBU AYAH DAN KEPERCAYAAN DIRI PADA REMAJA - Ernawati Ernawati; Galih Fajar Fadillah (Universitas Muhammadiyah Surakarta, 2018)
This study aims to determine the relationship between mother's role, father's role and self-confidence with social adjustment in adolescents. The research subjects of class IX Muhammadiyah Middle School 1 Surakarta numbered 110 people. Data collection uses social adjustment scale, father's role scale, mother's role scale, self-confidence scale. Data analysis calculations used three predictor regression analysis techniques and cross tabulation analysis. From the results of data analysis, there is a significant relationship between father's role, mother's role and self-confidence with social adjustment, which correlates the role of father to social adjustment = 23.8%; mother's role in social adjustment = 16.1%; confidence in social adjustment = 18.1%. The total effective contribution of father's role, mother's role and confidence in social adjustment is 58%.Penelitian ini bertujuan untuk mengetahui hubungan antara peran ibu, peran ayah dan kepercayaan diri dengan penyesuaian sosial pada remaja. Subjek penelitian siswa kelas IX SMP Muhammadiyah 1 Surakarta berjumlah 110 orang. Pengumpulan data menggunakan skala penyesuaian sosial, skala peran ayah, skala peran ibu, skala kepercayaan diri. Perhitungan analisis data menggunakan teknik analisis regresi tiga prediktor dan analisis tabulasi silang. Dari hasil analisis data menunjukkan terdapat hubungan signifikan antara peran ayah, peran ibu dan kepercayaan diri dengan penyesuaian sosial yang nilai korelasi peran ayah terhadap penyesuaian sosial = 23,8%; peran ibu terhadap penyesuaian sosial = 16,1%; kepercayaan diri terhadap penyesuaian sosial = 18,1%. Total sumbangan efektif peran ayah, peran ibu dan kepercayaan diri terhadap penyesuaian sosial sebesar 58%.